Les comportements écologiques des dirigeants des entreprises tunisiennes - Ahmed Turki (VertigO)
In 1988, some Tunisian firms, essentially in reaction with the environmental regulation, have instituted environmental initiatives. The objective of this research is to classify the Tunisian managers based on their environmental commitment. In a sample of 55 firms, the results show the existence of three groups based on environmental commitment; reactive, conformist and citizen managers. Firm size had a major impact on the environmental commitment. But no relationship was found between environmental commitment and activity sector.